Incidence of post-transplant glomerulonephritis and its impact on graft outcome - Jung Nam An; Jung Pyo Lee; Yun Jung Oh; Yun Kyu Oh; Jong-won Ha; Dong-Wan Chae; Yon Su Kim; Chun Soo Lim (Kidney Research and Clinical Practice, 2012)
Background: Herein, the significance of post-transplant glomerulonephritis (PTGN) has been revisited to investigate whether PTGN induces allograft failure. The aim of this study was to identify the incidence of PTGN and its association with allograft failure, as well as to analyze the risk factors for PTGN. Methods: Among the 996 Korean patients who underwent kidney transplantation in a multicenter cohort from 1995 to 2010, 764 patients were enrolled in this study. Results: The incidence rate of PTGN was 9.7% and 17.0% at 5 and 10 years of follow-up, respectively. PTGN was diagnosed in 17.8% of the recipients with results of biopsy tests or clinical diagnosis identifying glomerular diseases as the underlying cause, compared with 0.0%, 4.4%, 4.9%, 5.5%, and 5.7% of the recipients with renal vascular diseases, renal interstitial diseases/pyelonephritis/uropathy, diabetic renal disease, hereditary renal diseases, and diseases with unknown etiologies, respectively. Allograft survival was significantly decreased in patients with PTGN. PTGN was associated with a fourfold increase in graft failure with a hazard ratio of 7.11 for both acute rejection and PTGN. Results of the risk factor analysis for PTGN revealed that the underlying glomerular renal diseases and treatment methods using drugs such as tacrolimus and basiliximab significantly increased PTGN development, after adjusting for other risk factors. Conclusion: We conclude that PTGN is strongly associated with poor kidney allograft survival. Therefore, optimal management of recurrent or de novo GN should be the critical focus of post-transplant care.